Treating the Lips and Its Anatomical Correlate in Respect to Vascular Compromise - Ghannam, Sahar; Sattler, Sonja; Frank, Konstantin; Freytag, David L.; Webb, Katherine L.; Devineni, Aditya; Cotofana, Sebastian (Facial Plastic Surgery, 2019)
Treating the lips to increase facial attractiveness and youthfulness is challenging when trying to consider ethnic differences in an increasingly more diverse society. Multiple injection techniques are currently available for treating lip contour and volume, but a validation in the cadaveric model under the aspects of safety has not been performed yet. The injection techniques presented in this study are based on the experience and personal selection of the authors. The authors have assessed, treated, and evaluated for more than 20 years patients from the Middle East and Central Europe. Cadaveric verification was performed for each of the presented techniques to identify the positioning of the injected product inside the lips and its relation to the superior/inferior labial arteries. The results of the anatomic analyses revealed that in 58.3% of the performed injections, the product was placed close to the superior/inferior labial arteries. In 60.0% of the cases, applications using a needle placed the injected product in endangered locations, whereas 57.1% of the cases using cannulas placed the product in endangered locations (i.e., in the vicinity of the superior/inferior labial arteries). This anatomic study revealed that injected material into the lips is frequently placed in close proximity to labial arteries representing a high risk for intra-arterial applications, leading to tissue loss (necrosis) and potential end-arterial embolism (potential blindness). Nevertheless, treatment of the lips should be a multistep approach focusing first on the far (upper and middle face) and close (labiomandibular and labiomental) perioral regions.
Keywords: lips; contouring; volumizing; labial arteries; danger zone